Learning community and educational transformation: educational experiences of democratic participation - Izquierdo Medina, Giovanna; García Vallinas, Eulogio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Learning Communities are recognized for their strategies of inclusion and democratic participation. The objective of this text is to know the strategies of democratic participation that are carried out in a school constituted as a Learning Community. The results show the experiences of educational success, coexistence and involvement of the educational community that arise as a result of the transformation of the school towards a more inclusive and participatory project. In short, democratic participation represents an educational and claiming strategy that aims to end the inequalities that converge in educational spaces.